Cutting Edge : My Autobiography - Javed Miandad and Saad Shafqat; Foreword by Greig, Tony (Karachi Oxford University Press, 2004)
From the street of Karachi to the great Test centres of the world, the enigmatic Pakistani cricket hero Javad Miandad takes readers on a riveting journey through his many accomplishments as a player as well as a coach and not mincing words about his disappointments. Former England captain Tony Greig has written the foreword.
Include Illustration and Index.
It is biography of Javed Miandad.
Keywords: Pakistan -- Cricket players -- Miandad, Javed -- Cricket players -- Pakistan -- Biography